TRADISI WIWITAN: CARA PENYEBARAN DAN PROSES PEMBELAJARAN OLEH MASYARAKAT (Studi Kasus: Dusun Kedon Desa Sumbermulyo, Kecamatan Bambanglipuro, Kabupaten Bantul) - Selamet Eko Edy Saputro; Dwiningtyas Padmaningrum; Arip Wijianto (AGRITEXTS: Journal of Agricultural Extension, 2019)
The form of traditional knowledge that still persistence one is wiwitan tradition in Kedon Hamlet, Sumbermulyo Village, Bambanglipuro Subdistrict, Bantul Regency. The persistence of wiwitan tradition in Kedon Hamlet when the appreciation of cultural heritage generationsstarted to fade indicates that the presence of preservation efforts by the local community is still exist.Thisefforts can be done through learning and dissemination of wiwitan tradition by the local communities. Based on the idea this research aimed to; (1) determine how the communities of Kedon Hamlet, Sumbermulyo Village, Bambanglipuro Subdistrict Bantul Regency disseminate wiwitan tradition, (2) determine how the communities of Kedon Hamlet, Sumbermulyo Village, Bambanglipuro Subdistrict, Bantul Regencylearn wiwitan tradition. This research used a single case study method that examine the phenomenon of the persistence of wiwitan tradition. The data was collected by observation, documentation and indepth interview with informan. The determination informan conducted in purposive. Informan in the research are the head of Kedon Hamlet, chairman of the farmer groups, and the local communities. The data was analyzed using the model of interactive analysis Miles and Hubermen. This research showed that; (1) the communities of Kedon Hamlet disseminated wiwitan tradition in the form of cultural carnival, words of mouth and digital media, (2) the communities of Kedon Hamlet learned wiwitan tradition through social learning.